PROFIL PENYESUAIAN DIRI PESERTA DIDIK DALAM MENGENDALIKAN EMOSI DI LINGKUNGAN SEKOLAH KELAS XI SMA PGRI PADANG - Wati, Nila - (Bimbingan dan Konseling, 2014)
This Research was back grounded by the condition which is met in field where the student was too easy to get angry so that can make a fight among them. The students who always bother their friends, the student who always think that they were right, and the student who felt that uncomfortable in class. This research purpose is to describe : 1) The self adaptation profile of student in controlling emotion positively, 2) the profile of student adaptation in controlling emotion negatively. This research is descriptive and quantitative research. The population of this research is all students of class XI SMA PGRI I Padang, that consist of 220 students. The technique which is used in taking the sampling is professional random sampling. This sampling was taken 69 people for the first who are in class XI. The instrument which is used in this research is questionnaire, meanwhile for data analysis was used percentage technique. The result of this research said that : 1) the student profile of self adaptation in controlling emotion in school environment positively was good enough, 2) the student profile of self adaptation in controlling emotion in school environment negatively was good enough. The result of this research recommended to the student to be able to control their selves in emotion optimalize by controlling the attitude and act.